Shah Abdul Hannan: an exemplary human being and teacher - Hasan, Md. Mahmudul (Islamic Society of North America (ISNA), 2021)
When I first met Shah Abdul Hannan in 1994, I was a second-year university student and he was a senior civil services officer and well known for his honesty, efficiency, sincerity and important government posts. Although I have always been a “regular” person, he always made me feel honored both as a human being and as his student. We had many meetings and traveled together in Bangladesh and the U.K. I had long stays with him to benefit from his intellectual guidance and learn from his immense knowledge and insight, as well as to attend his classes and lectures. He never imposed his views on me or stopped me from expressing mine. A man of strong personality and force of character who respected others, his integrity manifested itself in his principled conduct, honest dealing and steady avoidance and disapproval of corruption and venality.